2016
DOI: 10.1074/jbc.m116.723973
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cholesterol Deficiency Attenuates Human Antigen R-linked Pro-inflammatory Stimulation via an SREBP2-linked Circuit

Abstract: Patients with chronic intestinal ulcerative diseases, such as inflammatory bowel disease, tend to exhibit abnormal lipid profiles, which may affect the gut epithelial integrity. We hypothesized that epithelial cholesterol depletion may trigger inflammation-checking machinery via cholesterol sentinel signaling molecules whose disruption in patients may aggravate inflammation and disease progression. In the present study, sterol regulatory element-binding protein 2 (SREBP2) as the cholesterol sentinel was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
1
8
1
Order By: Relevance
“…Fdft1 is a gene encoding for squalene synthase (SQS), which is the first enzyme in the committed cholesterol biosynthesis pathway (Figure 2a). In contrast to previous findings (Memon et al., 1997; Park et al., 2016), neither Srebf2 (Figure 3e) nor Fdft1 (Figure 3f) mRNA levels were decreased in cytokine‐treated gmASTRs and wmASTRs. Instead, transcripts of both Fdft1 and Srebf2 seemed to increase in cytokine‐treated gmASTRs and wmASTRs, indicating a potential compensatory mechanism for the decreased cholesterol efflux from both types of ASTRs.…”
Section: Resultscontrasting
confidence: 99%
“…Fdft1 is a gene encoding for squalene synthase (SQS), which is the first enzyme in the committed cholesterol biosynthesis pathway (Figure 2a). In contrast to previous findings (Memon et al., 1997; Park et al., 2016), neither Srebf2 (Figure 3e) nor Fdft1 (Figure 3f) mRNA levels were decreased in cytokine‐treated gmASTRs and wmASTRs. Instead, transcripts of both Fdft1 and Srebf2 seemed to increase in cytokine‐treated gmASTRs and wmASTRs, indicating a potential compensatory mechanism for the decreased cholesterol efflux from both types of ASTRs.…”
Section: Resultscontrasting
confidence: 99%
“…For example, immune pathway and cholesterol metabolism and homeostasis involve many of the same genes including ApoE, TREM2 and ABCA7. Recent studies suggested SREBP‐2 as a signaling hub integrating cholesterol metabolism with NLRP3 inflammasome assembly and inflammation activation , while SREBP‐2‐deficiency could also enhance pro‐inflammatory signals in response to inflammatory insults . Thus, SREBP‐2 dysregulation downstream to tau alterations could potentially cause broader detrimental effects than cholesterol dis‐homeostasis and amplify toxic effects of tau through additional pathways such as neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…22 Then m-SREBP migrates into the nucleus to activate its downstream genes involved in lipid biosynthesis as well as uptake. 23,24,44 The study by Cheng et al 45 reveals that the glycosylation of SCAP induced by glucose resulted in lipid accumulation in cancer cells. We did not check glycosylation of SCAP in NRK-52E cells.…”
Section: Discussionmentioning
confidence: 99%